-2x-3y=1

Simple and best practice solution for -2x-3y=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-3y=1 equation:


Simplifying
-2x + -3y = 1

Solving
-2x + -3y = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3y' to each side of the equation.
-2x + -3y + 3y = 1 + 3y

Combine like terms: -3y + 3y = 0
-2x + 0 = 1 + 3y
-2x = 1 + 3y

Divide each side by '-2'.
x = -0.5 + -1.5y

Simplifying
x = -0.5 + -1.5y

See similar equations:

| 5q=315 | | y^11+6=-7 | | 2+2x=4x-8 | | -4x-12y=36 | | y^3+5=-7 | | -16t^2-11t+150=0 | | 3x-12y=27 | | -5(-3q+11)+4(-1-5q)= | | -8p-2p=3+1-6p-5p | | 9n^2-3n=2 | | 3y+3x=36 | | 64n^2=49 | | 5n^2=20n | | 5x^2-1=3 | | 6n^3-22n^2=3n-11 | | -8x+7x=9 | | 2x-3y=-18 | | 27s^7/49s*21s^6/243s | | T=5s+18.38 | | 34x=17x+9 | | 1x+1x+7=2x+3 | | 5x^2+2x-7/2x^2-7x-4/25x^2+55x+28/2x^2+3x+1 | | 5ab-a+3ab-ab= | | -2x+4y=28 | | -6/7=3x+1/2 | | y=4/5x+6 | | 3x-25=-19+x | | -9.8+(-3.7)= | | 18y-13y=25 | | 3(2x-4)=10x+3-x | | 23=9 | | 9x^2-11=6a |

Equations solver categories